If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -31 = 7x + 4 Reorder the terms: -31 + 11x = 7x + 4 Reorder the terms: -31 + 11x = 4 + 7x Solving -31 + 11x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -31 + 11x + -7x = 4 + 7x + -7x Combine like terms: 11x + -7x = 4x -31 + 4x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 -31 + 4x = 4 + 0 -31 + 4x = 4 Add '31' to each side of the equation. -31 + 31 + 4x = 4 + 31 Combine like terms: -31 + 31 = 0 0 + 4x = 4 + 31 4x = 4 + 31 Combine like terms: 4 + 31 = 35 4x = 35 Divide each side by '4'. x = 8.75 Simplifying x = 8.75
| y-1/y-3=(y-1/y+5)+1 | | 17/3x+3/5=8/3x | | X^1/3-2=0 | | 2x^4-2=160 | | 6x-13=3(2x+9) | | y=-4/x+3 | | 8t-26=-30 | | 21/25=x/75 | | 7y=2+5x | | 2v+26=6v+30 | | 4(3y-2)+2(3y-2)= | | (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x | | 2x-2(6-4x)=6(x-5)-26 | | f-(41/3)=10 | | 12k+131=3(4k+43) | | 0=-16x^2+40x+2 |